Digital urban network connectivity: Global and Chinese internet patterns1. (21st January 2014) - Tranos, Emmanouil; Kourtit, Karima; Nijkamp, Peter
Abstract Cities are not only connected through conventional infrastructure, but also through digital infrastructure. This paper tests whether digital connectivity patterns follow traditional ones. Using a generalized spatial interaction model, this paper shows that geography (and distance) still matters for an extensive set of world cities. With a view to the rapidly rising urbanization, the attention is next focused on the emerging large cities in China to test the relevance of distance frictions − next to a broad set of other important explanatory variables − for digital connectivity. Various interesting results are found regarding digital connectivity within the Chinese urban system, while also here geography appears to play an important role.